2018
DOI: 10.1126/science.aar7854
|View full text |Cite
|
Sign up to set email alerts
|

A DNA methylation reader complex that enhances gene transcription

Abstract: DNA methylation generally functions as a repressive transcriptional signal, but it is also known to activate gene expression. In either case, the downstream factors remain largely unknown. By using comparative interactomics, we isolated proteins in Arabidopsis thaliana that associate with methylated DNA. Two SU(VAR)3–9 homologs, the transcriptional anti-silencing factor SUVH1, and SUVH3, were among the methyl reader candidates. SUVH1 and SUVH3 bound methylated DNA in vitro, were associated with euchromatic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
165
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(181 citation statements)
references
References 61 publications
13
165
2
1
Order By: Relevance
“…We noted that a similar study was recently published online when we were preparing our paper (Harris et al 2018). The published study reported that SUVH1 and SUVH3 interact with DNAJ1 and DNAJ2 (which are corresponding to SDJ1 and SDJ2, respectively, in our study) and thus form a complex that enhances gene transcription; the main conclusions reported in the published study are confirmed by our independent study.…”
Section: Discussionsupporting
confidence: 87%
“…We noted that a similar study was recently published online when we were preparing our paper (Harris et al 2018). The published study reported that SUVH1 and SUVH3 interact with DNAJ1 and DNAJ2 (which are corresponding to SDJ1 and SDJ2, respectively, in our study) and thus form a complex that enhances gene transcription; the main conclusions reported in the published study are confirmed by our independent study.…”
Section: Discussionsupporting
confidence: 87%
“…These three DnaJ‐domain proteins were also pulled down, along with SUVH3 and SUVH1 in a DNA‐trap experiment using methylated MEMS as a probe, wiht unmethylated MEMS as a control (Figure B). During the preparation of this manuscript, Harris and colleagues also identified SUVH1, SUVH3 and DnaJ proteins as components of a DNA methylation reader complex that activates gene expression (Harris et al ). It is interesting to note that in this issue of the Journal , Zhao and colleagues show SUVH1 and SUVH3 function synergistically with these DnaJ proteins to prevent promoter methylated genes from silencing (Zhao et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Xiao et al found 1674 hyper‐methylated regions (HMRs) in suvh1/3/7/8 quadruple mutant compared to Col‐0. Interestingly, in all of the three studies, they observed reduced ROS1 expression in suvh1/3 , sdj1/2 , and sdj 1/2/3 mutants (Harris et al ; Xiao et al ; Zhao et al ). Reduced ROS1 expression is usually associated with increase of DNA methylation at ROS1 target loci.…”
mentioning
confidence: 94%
“…This protein complex regulates ROS1 expression through binding to the methylated MEMS sequence that is known to be guided by the RdDM pathway (Lei et al ). The regulation of ROS1 expression by the SUVH‐SDJ complex was confirmed by whole‐genome chromatin immunoprecipitation assay sequencing and RNA‐seq analyses (Harris et al ; Zhao et al 2019). In the study of Xinjian He's group, they found that SUVH‐SDJ protein complex can also bind many other highly methylated genomic regions, which are predominantly methylated by the RdDM pathway.…”
mentioning
confidence: 96%
See 1 more Smart Citation